The Bigamist - Young, F. E. Mills (Florence Ethel Mills), 1875- (Salt Lake City, UT : Project Gutenberg, 2011)
"The Bigamist" by F.E. Mills Young is a novel written in the early 20th century. The story revolves around the lives of Herbert Arnott and his wife Pamela, focusing on the complexities of their marriage against the backdrop of a deeply troubling revelation: Herbert has another wife whose existence he has concealed. The main characters grapple with themes of love, deception, and societal norms, as the stability of their seemingly happy life begins to unravel. At the start of the novel, readers are introduced to Herbert and Pamela Arnott on the eve of their fifth wedding anniversary. Herbert appears troubled and preoccupied, while Pamela is blissfully content with their life together. As they share intimate moments and reflect on their happiness, a shadow looms closer, represented by the arrival of a letter that Pamela discovers later. This letter reveals that Herbert previously had another marriage, throwing their bond and Pamela's understanding of her identity into chaos. The opening chapters set the stage for a turbulent emotional journey, as Pamela must navigate the painful truth of her husband's past and the implications it poses for their future. (This is an automatically generated summary.)
Release date is 2011-08-29
Produced by Nick Hodson of London, England
Keywords: Bigamy -- Fiction; Man-woman relationships -- Fiction; British -- South Africa -- Fiction